The Status and Marital Satisfaction Factors in Nulliparous Pregnant Females Attending Clinics in Asadabad City during Years 2015 and 2016 - batol khodakarami; Seyedeh Zahra Masoumi; roya asadi (Hamadan University of Medical Sciences, 2017)
Introduction: Pregnancy is an important event that occurs in the lives of most females. Marital satisfaction is a very important aspect in this period that influences quality of life and physical and mental health of females and their children. Marital satisfaction is influenced by a variety of factors. In this study, we investigated the factors influencing marital satisfaction during this period. Methods: This descriptive study was conducted on 120 cases that were randomly selected among pregnant females attending clinics of Asadabad during year 2015. Data was gathered by an information form, Enrich Marital Satisfactions Questionnaires and demographic questionnaires. Questionnaires were filled by the participants. The data was analyzed by SPSS 16 software using mean and standard deviation, independent t test, and Analysis of Variance (ANOVA). Results: Level of marital satisfaction in pregnant females was medium and high. Sub scales of conflict resolution and character issues and equality were lower than the rest of the scales. Subscales of ideal distortion, relatives and friends, and religious orientation were higher than the rest of the scales. Also, there was a significant relationship between education, career, husband's occupation, household income, job stability of the spouse, planned pregnancy, infertility history, length of marriage, age of the woman and marital satisfaction (P < 0.05). Conclusions: Life skills counseling can be effective in improving marital satisfaction. Demographic variables were predictors of marital satisfaction in pregnant females.